Development of Interactive Powerpoint Media in Science Learning to Improve Primary Students Critical Thinking Ability - Septi Dhea Kusuma; Wahyudi Wahyudi (JURNAL PENDIDIKAN IPS, 2024)
Teacher Center based learning results in not maximizing critical thinking skills. There is a lack of interesting interactive PowerPoint-assisted learning media in science learning to improve critical thinking skills. This research aims to develop and demonstrate the effectiveness of interactive PowerPoint media in science and science learning to improve elementary school students' critical thinking skills. The research was carried out using the ADDIE development with a total of 20 samples taken in class 4. Data collection techniques used were questionnaire collection, observation, interviews, pre-test and post-test with quantitative descriptive analysis techniques. The results of the research before using interactive PowerPoint, students got an average score of 56%, and after implementing interactive PowerPoint media they got an average score of 79.5% with the results of the analysis after using media to improve critical thinking skills getting a percentage of 84.37%. It can be concluded that interactive PowerPoint media is effectively used to improve students' critical thinking skills.